2010
DOI: 10.1002/pssa.200925311
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on upconversion luminescence in Yb3+/Er3+‐codoped Gd2SiO5 single crystal

Abstract: Yb 3þ /Er 3þ -codoped Gd 2 SiO 5 (Yb,Er:GSO) single crystal was grown by the Czochralski method. The upconversion properties of the crystal under 940 nm excitation were investigated. Intense emission bands centered at 521, 548, and 652 nm corresponding to the transitions 2 H 11/2 ! 4 I 15/2 , 4 S 3/2 ! 4 I 15/2 , and 4 F 9/2 ! 4 I 15/2 of Er 3þ , respectively, were observed at room temperature. The dependence of the intensity of the Er 3þ emission on the pump power and possible upconversion mechanism were disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…To further clarify our understanding of the luminescence process in the Tm 3+ /Er 3+ /Yb 3+ ‐doped YSZ crystals, the luminescence spectra of the x = 0.150 mol% sample was investigated at different laser pump powers, as shown in Figure . The upconversion luminescence intensity (Iup${I_{{\rm{up}}}}$) is related to the excitation power ( P ) [Equation (3)] [ 35,36 ] IupPn\begin{equation}{{\rm{I}}_{up}} \propto {{\rm{P}}^n}\end{equation}where n is the number of photons needed to generate the excited state.…”
Section: Resultsmentioning
confidence: 99%
“…To further clarify our understanding of the luminescence process in the Tm 3+ /Er 3+ /Yb 3+ ‐doped YSZ crystals, the luminescence spectra of the x = 0.150 mol% sample was investigated at different laser pump powers, as shown in Figure . The upconversion luminescence intensity (Iup${I_{{\rm{up}}}}$) is related to the excitation power ( P ) [Equation (3)] [ 35,36 ] IupPn\begin{equation}{{\rm{I}}_{up}} \propto {{\rm{P}}^n}\end{equation}where n is the number of photons needed to generate the excited state.…”
Section: Resultsmentioning
confidence: 99%
“…Pure and doped R 2 SiO 5 crystals have been previously grown using the Czochralski [33,[38][39][40][41][42][43][44][45][46][47], flux [19,29,41,[48][49][50], micropulling-down [51,52] techniques. Er 2 SiO 5 crystals were also obtained when attempting to synthesize the intermetallic compound ErFeRe [32].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there is a large spectrum overlap between the 2 𝐹 5/2 → 2 𝐹 7/2 of Yb 3+ NIR emission and the 4 𝐼 15/2 → 4 𝐼 11/2 of Er 3+ absorp-tion bands, which results in an efficient nonradiative energy transfer process and in turn efficient upconversion emission. [6] Host materials for Er 3+ ions play an important role in obtaining high-efficient upconversion signals, due to the different crystal fields caused by structure symmetry of the host materials would contribute to different perturbation terms for the Er 3+ and Yb 3+ inner shell transitions. [7,8] In a series of papers, many reseachers have studied the influence of excitedstate re-absorption loss on the green laser emission in transition 2 𝐻 11/2 → 4 𝐼 15/2 and 4 𝑆 3/2 → 4 𝐼 15/2 pumped by various mechanisms.Zhang et al [9] have already successfully reported optical gain and upconversion luminescence in LaF 3 :Er 3+ /Yb 3+ nanoparticledoped organic-inorganic hybrid materials in waveguide amplifier.…”
mentioning
confidence: 99%